Encapsulation of Pyrene-Functionalized Poly(benzyl ether) Dendrons into a Water-Soluble Organometallic Cage - Pitto-Barry, Anaïs; Barry, Nicolas P. E.; Zava, Olivier; Deschenaux, Robert; Therrien, Bruno (My University, 2011)
Two generations of lipophilic pyrenyl functionalized poly(benzyl ether) dendrimers (P1 and P2) have been synthesized. The thermal properties of the two functionalized dendrimers have been investigated, and the pyrenyl group of the dendritic molecules encapsulated in the arene–ruthenium metalla-cage, [Ru6(p-cymene)6(tpt)2(donq)3]6+ ([1]6+) (tpt=2,4,6-tri(pyridin-4-yl)-1,3,5-triazine; donq=5,8-dioxydo-1,4-naphthoquinonato). The host–guest properties of [P1⊂1]6+ and [P2⊂1]6+ were studied in solution by NMR and UV/Vis spectroscopic methods, thus allowing the determination of the affinity constants. Moreover, the cytotoxicity of these water-soluble host–guest systems was evaluated on human ovarian cancer cells.
Keywords: anticancer compounds; dendrimer; drug delivery; host–guest chemistry; metalla-cage